Marianne E. Kalinke & P. M. Mitchell: Bibliography of old Norse-Icelandic Romances. Islandica 44 (Cornell University Press, 1985). xii + 140 s., 30,25 . - Balle, Søren (Historie/Jyske Samlinger, 1989)
-